Drying turmeric slices using a photovoltaic ventilation direct solar dryer: Drying characteristics and interactions of heat and mass transfer - Bambang Waluyo Hadi Eko Prasetiyono; Suherman Suherman; Bakti Jos; Muhammad Anas Asy-Syaqiq (International Journal of Renewable Energy Development, 2026)
This study compares the drying characteristics and the heat and mass transfer phenomena while drying turmeric slices using a photovoltaic ventilation direct solar dryer and open sun drying. Turmeric slices of varying thicknesses—5, 7, and 10 mm—were dried from 83.48% to a final moisture content of 5–6% to ensure safe storage conditions. The drying times required were 1440, 1800, and 2160 min for the direct solar dryer, and 2220, 2520, and 2880 min for open sun drying at 5, 7, and 10 mm thicknesses, respectively. Drying Turmeric slices using the direct solar dryer at thinner thicknesses showed a faster drying rate, with the highest average drying rate observed for the 5 mm slices at 0.287 g/min. Similarly, drying efficiency was higher for thinner slices. The Midilli model provided the best fit for experimental and predicted data in describing the drying kinetics of turmeric slices. The effective moisture diffusivity obtained in this study was 1.65 × 10⁻⁸, 2.66 × 10⁻⁸, and 4.11 × 10⁻⁸ m2/s for the direct solar dryer, and 0.89 × 10⁻⁸, 1.52 × 10⁻⁸, and 2.38 × 10⁻⁸ m2/s for open sun drying at 5, 7, and 10 mm thicknesses, respectively. Higher heat and mass transfer coefficients were observed for drying thinner turmeric slices using the direct solar dryer. The convective heat transfer and evaporative heat transfer coefficients decreased as the moisture content was reduced. In contrast, the mass transfer coefficient increased as the drying time progressed.